(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
Peanut (Arachis hypogaea L.) cultivation is an agricultural product of great nutritional and economic importance. The grain is rich in oil, proteins, carbohydrates, fiber and ash, which makes it attractive to the human diet, in addition to contributing to the agricultural and industrial development of various countries due to the large volume produced. Peanut production is affected by the proportion of macronutrients present in the soil, which influence the yield, quality and growth of plants. Therefore, the objective of this work was to carry out a bibliographic review related to the importance of macronutrients in peanut cultivation. A search was carried out for scientific articles published during the period 2014-2024 in the Dialnet, Redalyc, Scielo and Google Scholar databases, which generated 47 documents related to the function of nutrients and the importance and dosage of fertilization for peanut cultivation. It was shown that the macronutrients nitrogen, phosphorus, potassium, sulfur and calcium are essential for peanut cultivation due to the specific role they play in plant metabolism that affects production and yield, requiring an external source and consideration of the factors that influence their absorption to achieve profitable development.